Efektivitas Bantuan Pangan Non Tunai (BPNT) dalam Program E-Waroeng Kepada Masyarakatdesa Tanjung Baru Kecamatan Cikarang Timur Kabupaten Bekasi - Ruslan Nurhasan; Kusrin Kusrin; Hanny Purnamasari (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research departs from a problem of inaccuracy in the distribution of non-cash cash assistance (BPNT) in the KUBE PKH E-waroeng Program in Tanjung Baru Village. The purpose of this study was to determine the effectiveness of the implementation of non-cash food assistance (BPNT) in the KUBE PKH E-waroeng Program in Tanjung Baru Village, East Cikarang District, Bekasi Regency. This research uses descriptive qualitative method. Data collection techniques used are interviews, observation, documentation. The data was taken from a predetermined number of 6 people. This study uses the theory of Budiani's Effectiveness (in Pratiwi and Nurcahyo 2017) namely the Accuracy of Program Targets, Program Socialization, Program Objectives and Program Monitoring. The results of this study indicate that there are several factors that make the implementation of non-cash food assistance (BPNT) in the E-waroeng KUBE PKH program not yet on target in Tanjung Baru Village, namely the data renewal process that has not been maximized which resulted in the distribution of BPNT in the E-waroeng KUBE PKH program. has not been distributed to recipients who are entitled to this assistance and the lack of public knowledge in the distribution of BPNT in the KUBE PKH E-waroeng program.